EMPOWERING COMMUNITIES THROUGH MENTAL HEALTH FOR A SUSTAINABLE FUTURE - Bhutiar, Peden (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The integration of mental health into the 2030 Agenda Sustainable Development Goals (SDGs) in the global narrative highlights the importance of mental health and well-being that goes beyond economic growth and physical health. Mental health is not just an isolated goal within SDG 3 (Good Health and Well-being), but a crucial, consistent factor that influences all aspects of sustainability that United Nations member states are striving to achieve. This paper explores the influence of mental health on key areas such as social equity, quality education, and peace and justice, as stated in the United Nations' 2030 Agenda for Sustainable Development. It highlights the increasing recognition of mental health as a fundamental human right and a primary factor in social change, resilience building, and overall well-being. The findings highlight the urgent need for an integrated, multi-sectoral approach, that should focus on universal health coverage, community-based interventions, stigma reduction, and the development of comprehensive data systems as core strategies to ensure a balanced approach that promotes the well-being of current and future generations.